Estrategia de marketing digital para maximizar las ventas en Isla Fosil en la ciudad de Babahoyo 2023. - Alvarado Chacón, Erick Daniel (2024)
This case study highlights the importance of marketing and the relevance of having a digital marketing plan through social networks in the company Isla Fossil in the city of Babahoyo, this company is dedicated to the commercialization of jewelry accessories among other items and offers technical assistance service. Currently we see the growth that the use of digital media has had and how marketing campaigns have been complemented to social networks. Today, the company's knowledge has the duty to be where its customers or consumers are, to apply planned and well-executed digital strategies in order to reach its objectives or goals successfully. We apply various types of research such as descriptive, qualitative and quantitative, allowing the analysis of the company's weak points, with the intention of positioning the company in the market, generating sales and developing a relationship with customers, through digital marketing strategies, generating a content plan, advertising campaigns through its social networks and the creation of a website with attractive content for customers.